Profile of high order thinking skills (HOTS) in create level of SMA students on biology learning material at Banten Province - Eka Afriyana; Ika Rifqiawati; Mahrawi Mahrawi; Mila Ermila Hendriyani; Dwi Ratnasari (Journal on Biology and Instruction, 2021)
Higher order thinking skills are needed in 21st century learning. This study aims to determine the profile of higher order thinking skills at the level of creating biology subjects for high school students in Banten Province and a comparison of students' creative abilities in each district/city in Banten Province. The research method used was a phenomenological approach and school sampling with random sampling technique was used in 8 cities or districts of Banten Province in March-October 2020. Data were collected using a questionnaire technique. The data collection instrument is a questionnaire. The data analysis technique uses the Miles & Huberman model. Based on the results of the study, it was shown that the higher-order thinking ability of students at the creative level in Banten Province was 6.8 which was included in the very poor category. The learning process that has not taken the HOTS approach and is not used to providing students with high-level thinking questions makes students find it difficult to solve the problems they face.